Principles of management - Norlida Kamaluddin 1965-; Za'faran Hassan; Rabiah Abdul Wahab; Rohaya Mohd Hussein (Oxford Fajar Sdn. Bhd., 2014)
The second edition of Principles of Management is a valuable and relevant resource for both undergraduates pursuing courses in business and economics as well as educators of management. Spanning 17 comprehensive chapters which adhere closely to the syllabus recommended by major universities in Malaysia, this revised and updated edition provides students with the fundamentals of management. It is hoped that this textbook will contribute significantly to the education and preparation of tomorrow's managers.